Mechanism of race-dependent platelet activation through the PAR4 and Gq signaling axis - Tourdot, Benjamin E. (Arterioscler Thromb Vasc Biol, 2014)
OBJECTIVE: Black individuals are at an increased risk of myocardial infarction and stroke, two vascular diseases with strong thrombotic components. Platelet activation is a key step in platelet clot formation leading to myocardial infarction and stroke and recent work supports a racial difference in platelet aggregation through the thrombin protease-activated receptors (PARs). The underlying mechanism for this racial difference, however has not been established. Determining where in the signaling cascade these racial differences emerge will aid in understanding why individuals of differing racial ancestry may possess an inherent difference in their responsiveness to anti-platelet therapies. APPROACH AND RESULTS: Washed human platelets from black volunteers were hyper-aggregable in response to PAR4-mediated platelet stimulation compared to whites. Interestingly, the racial difference in PAR4-mediated platelet aggregation persisted in platelets treated ex vivo with aspirin and 2MeSAMP, suggesting that the racial difference is independent of secondary feedback. Further, stimulation of platelets from black donors with PAR4-activating peptide (PAR4-AP) showed a potentiated level of activation through the G(q) pathway compared to platelets from white donors. Differences in signaling included increased Ca(2+) mobilization, Rap1 activation, and integrin αIIbβ3 activation with no observed difference in platelet protein expression between the groups tested. CONCLUSIONS: Our study is the first to demonstrate that the G(q) pathway is differentially regulated by race following PAR4 stimulation in human platelets. Furthermore, the racial difference in PAR4-mediated platelet aggregation persisted in the presence of COX and P2Y(12) dual inhibition, suggesting that current anti-platelet therapy may provide less protection to blacks than whites.